The Histologic Alterations in Rat Kidneys Induced By Experimental Diabetes - Kuloglu, Tuncay; Dabak, Duerrin Oezlem (Ortadogu Ad Pres & Publ Co, 2009)
Objective: We studied on the effect of the streptozotocin-induced diabetes mellitus on kidney tissues of rats at 2nd, 4th and 6th weeks after induction of diabetes to determine the importance of the alterations that occur in the kidneys in the early phase of the diabetic nephropathy. Material and Methods: Fifty-four adult male Wistar rats were used in this study. Rats were divided into mainly 3 groups as; control group (n= 3 x 6), control group to which 0.1 M phosphate-sitrate was given intraperitoneally (n= 3 x 6) and diabetic group to which 50 mg/kg streptozotocin was given intraperitoneally (n= 3 x 6). Six rats from each group were decapitated at the end of the 2(nd), 4(th) and 6(th) weeks and the kidneys of the rats were removed. Tissue samples were processed by using routine paraffin techniques. Paraffin sections were stained using Haematoxylin and eosin, Masson thrichrom, toluidine blue, Periodic acid-schiff, and the specimens were examined under the light microscope. Results: There was no difference between the control groups in the histological examination. However, towards the 6(th) week of the experiment, histopathologic changes gradually increased in the diabetic group, such as glomerular hypertrophy, increment in mesangial matrix and cells, thickening of basement membrane of the glomerular capillaries, detachment and degeneration of the brush border of the tubular epithelium and Armanni-Ebstein lesions. Conclusion: In this study, we determined that histopathologic changes in the kidney tissues of rats gradually increased in proportion with the duration of experimental diabetes.
Keywords: Diabetes mellitus, experimental; kidney; rats